2020
DOI: 10.1001/jamaoncol.2019.3702
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization Plus Chemotherapy for First-line Treatment of Locally Advanced Intrahepatic Cholangiocarcinoma

Abstract: Radioembolization plus chemotherapy as first-line treatment of locally-advanced intrahepatic cholangiocarcinoma. The multi-center single-arm phase 2 MISPHEC study (14) Radiology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(220 citation statements)
references
References 43 publications
6
179
0
4
Order By: Relevance
“…Of note, only a minority of patients had impaired liver function in our cohort reflected by normal bilirubin levels in most patients. Interestingly, Edeline et al found carcinoembryogenic antigen (CEA) to be a prognostic factor in advanced ICC undergoing combined radioembolization and chemotherapy [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, only a minority of patients had impaired liver function in our cohort reflected by normal bilirubin levels in most patients. Interestingly, Edeline et al found carcinoembryogenic antigen (CEA) to be a prognostic factor in advanced ICC undergoing combined radioembolization and chemotherapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the advent of new chemotherapy regimens with improved survival rates [6], immunotherapies, as well as improved patient selection, promise novel multimodal treatment options when combined with 90 Y TARE for the treatment of ICC [27][28][29]. The first prospective trial combining radioembolization and chemotherapy (again with cisplatin and gemcitabine), which was recently published, reported a median overall survival of 22 months following combined treatment [25]. The improved survival rates in this study compared to our cohort is attributed again to the much-advanced tumor stages and similarly increased morbidity in our cohort, having undergone already multiple therapies, while the study cohort of Edeline et al were all therapy-naïve when included in the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative agents such as bintrafusp alfa (M7824), a bifunctional monoclonal antibody targeting transforming growth factor-beta trap and anti-PD-L1, have been explored in pre-treated biliary tract cancers and granted orphan drug designation by the FDA, based on promising phase I findings (ORR of 20% in unselected biliary tract cancer population). 42 Other therapeutic options: liver-directed therapies and immunotherapy For selected patients with liver-predominant or locally advanced disease, strategies involving liverdirected therapies [43][44][45][46] and external beam radiotherapy 47 are being explored, respectively. Ongoing clinical trials are likely to elucidate the role of such approaches (for example: ABC-07, EudraCT 2014-003656-31 and SIRCCA, NCT02807181).…”
Section: Current State Of Playmentioning
confidence: 99%
“…60 Pre-surgical selective internal radiation therapy (SIRT) in iCCA has shown promising preliminary results in terms of safety and effectiveness, 61,62 even in association with chemotherapy, in the treatment of advanced iCCA. 63 In a study on 45 patients with unresectable iCCA, Yttrium 90 (Y 90 ) SIRT combined with gemcitabine and/or platinum chemotherapy achieved an 18% rate of conversion to free-margin surgery with no significant toxicity. 62 An example of efficacy of such combination treatment is presented in Fig.…”
Section: Role Of Neoadjuvant Therapies From a Surgical Perspectivementioning
confidence: 99%